2018
DOI: 10.1093/mnras/sty1949
|View full text |Cite
|
Sign up to set email alerts
|

Reionization in Technicolor

Abstract: We present the Technicolor Dawn simulations, a suite of cosmological radiationhydrodynamic simulations of the first 1.2 billion years. By modeling a spatiallyinhomogeneous UVB on-the-fly with 24 frequencies and resolving dark matter halos down to 10 8 M ⊙ within 12h −1 Mpc volumes, our simulations unify observations of the intergalactic and circumgalactic media, galaxies, and reionization into a common framework. The only empirically-tuned parameter, the fraction f esc,gal (z) of ionizing photons that escape t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
112
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 167 publications
11
112
1
Order By: Relevance
“…The impact of radiative feedback is less important in the CROC simulations than in CoDa. Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017: the Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017 LF results are based on a cosmological simulation of galaxy formation in a h 7.5 1 3 -( ) Mpc 3 volume of the universe including both gravity and hydrodynamics as implemented in the GADGET-3 code (Springel 2005). To this code, gas cooling is added through collisional excitation of hydrogen and helium as in Katz et al (1996), and metal line cooling is implemented using the collisional ionization equilibrium tables of Sutherland & Dopita (1993).…”
Section: Comparison With Theoretical Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of radiative feedback is less important in the CROC simulations than in CoDa. Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017: the Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017 LF results are based on a cosmological simulation of galaxy formation in a h 7.5 1 3 -( ) Mpc 3 volume of the universe including both gravity and hydrodynamics as implemented in the GADGET-3 code (Springel 2005). To this code, gas cooling is added through collisional excitation of hydrogen and helium as in Katz et al (1996), and metal line cooling is implemented using the collisional ionization equilibrium tables of Sutherland & Dopita (1993).…”
Section: Comparison With Theoretical Expectationsmentioning
confidence: 99%
“…Star formation is added using the Kennicutt-Schmidt law, with supernovae feedback included following the "ezw" prescription from Davé et al (2013) and metal enrichment from supernovae as implemented as in Oppenheimer & Davé (2008). Flattening in the Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017 LFs occurs mostly due to less efficient gas cooling at lower halo masses.…”
Section: Comparison With Theoretical Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical and analytical models of the early Universe (e.g., Gnedin & Ostriker 1997;McQuinn et al 2007;Robertson et al 2010;Haardt & Madau 2012;Finlator et al 2018;Katz et al 2019) reproduce the observed completion of hydrogen reionization around a redshift, z, of ∼ 6 (Fan et al 2006b). However, to achieve this, the models require that a large fraction of the produced ionizing photons escape the host galaxies and reach the IGM.…”
Section: Introductionmentioning
confidence: 97%
“…z < 4.5 DLAs n512RT64 simulation at z = 5(Finlator et al 2018) volatile elements at z < 4.5 volatile elements at z > 4.5 N HI -weighted mean metallicity for median z=4.83 Metallicity evolution with redshift. The red dots with blue error bars are the binned N H I -weighted mean metallicities of DLAs at z < 4.5 using volatile elements from the literature, with each bin containing 16 or 17 DLAs and the solid blue line showing the corresponding best fit.…”
mentioning
confidence: 99%